PREPARATION OF BITTER GOURD READY-TO-SERVE BEVERAGE AND EFFECT OF STORAGE TEMPERATURE ON ITS KEEPING QUALITY - K. P. SATKAR; P. R. CHALKE (The Bioscan, 2012)
Bitter gourd ready-to-serve (RTS) beverage was prepared by optimizing the levels of fruit juice, sugar and citric acid and also keeping quality of RTS beverage was studied. The fresh bitter gourd RTS had on an average 13.00º Brix TSS, 0.3 per cent titratable acidity, 4.50 per cent reducing sugars and 9.80 per cent total sugars. The recipe for fresh RTS was standardized as juice 15mL, sugar 15g, citric acid 0.29 g and water 76mL. It was observed that there was overall increase in TSS and reducing sugars, while decrease in acidity and total sugars content during storage of RTS beverage at ambient (27± 5ºC) and refrigerated (5±1ºC) temperature. The score for overall acceptability of bitter gourd RTS also decreased during storage. The RTS with stored at refrigerated temperature was found to be more acceptable after 3 months of storage.